2010
DOI: 10.1097/ede.0b013e3181c9fbb3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Contraceptives in Pregnancy and Major Structural Birth Defects in Offspring

Abstract: Previous reports of associations between OC use and specific types of anomalies were not corroborated. Given that associations were assessed for 32 types of birth defects, our findings of 2 increased associations between OC use and gastroschisis and hypoplastic left heart syndrome should be interpreted as hypotheses until they can be evaluated further. Overall, our findings are consistent with the majority of previous studies that found women who use OCs during early pregnancy have no increased risk for most t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
2
35
0
2
Order By: Relevance
“…Estudo húngaro de caso-controle, abrangendo 537 casos, observou risco aumentado de defeitos nos membros de 1,7 vez 32 . No entanto, estudo caso-controle multicêntrico realizado nos Estados Unidos concluiu que mulheres que usam contraceptivos orais durante o início da gravidez não têm risco aumentado para a maioria dos tipos de más-formações congênitas maiores 33 . Em uma meta-análise, envolvendo 12 estudos prospectivos, Bracken 34 também concluiu que os contraceptivos orais não foram associados com risco aumentado de defeitos cardíacos congênitos e defeitos de redução de membros.…”
Section: Discussionunclassified
“…Estudo húngaro de caso-controle, abrangendo 537 casos, observou risco aumentado de defeitos nos membros de 1,7 vez 32 . No entanto, estudo caso-controle multicêntrico realizado nos Estados Unidos concluiu que mulheres que usam contraceptivos orais durante o início da gravidez não têm risco aumentado para a maioria dos tipos de más-formações congênitas maiores 33 . Em uma meta-análise, envolvendo 12 estudos prospectivos, Bracken 34 também concluiu que os contraceptivos orais não foram associados com risco aumentado de defeitos cardíacos congênitos e defeitos de redução de membros.…”
Section: Discussionunclassified
“…Although unaware usage of oral contraceptives in the early stages of pregnancy was claimed to cause VACTERL (Vertebral anomalies, Anal atresia, Cardiac defects, Tracheoesophageal fistula and/or Esophageal atresia, Renal & Radial anomalies and Limb defects) syndrome in the 1970s, these findings were proven later to be incorrect in well-controlled and unbiased epidemiologic studies (Harlap, Shiono & Ramcharan, 1985;Baumann, Greinacher, Emmrich, & Spranger, 1976). In recent years, Waller et al's study (2010), similarly to other previous studies proved that no increase was observed in most types of congenital malformation in women usage of OCs during early pregnancy (Waller et al, 2010). That is why, by counseling the women on the benefits, side-effects and risks of OC use, and how to take the tablets correctly and compliantly, prevent unwanted pregnancies; OCs can impact significantly on women's lives.…”
Section: )mentioning
confidence: 86%
“…Hormonal contraceptive methods do not have any known associated teratogenic or abortifacient effects. [15][16][17] If it has been less than 5 days since unprotected intercourse, it is reasonable to offer a woman emergency contraception and then have her start her method immediately after. A follow-up pregnancy test in 2 to 4 weeks should be performed.…”
Section: Contraceptive Methods Initiationmentioning
confidence: 99%